2018
DOI: 10.1093/ibd/izy079
|View full text |Cite
|
Sign up to set email alerts
|

Gene Signature–Based Approach Identified MEK1/2 as a Potential Target Associated With Relapse After Anti-TNFα Treatment for Crohn’s Disease

Abstract: Our data revealed the abnormalities in anti-TNFα responders' CD colons that would be cause of recurrence of CD. Also, we provided evidence regarding MEK1/2 inhibitor as a potential treatment against CD to achieve sustainable remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…8a and Supplementary Table 1 ). These data are consistent with findings from Gamo et al demonstrating elevated SPRY2 expression in adult IBD patients 43 . Furthermore, in our mucosal biopsy samples, SPRY2 levels were inversely correlated with IL33 expression (Fig.…”
Section: Resultssupporting
confidence: 93%
“…8a and Supplementary Table 1 ). These data are consistent with findings from Gamo et al demonstrating elevated SPRY2 expression in adult IBD patients 43 . Furthermore, in our mucosal biopsy samples, SPRY2 levels were inversely correlated with IL33 expression (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained from analysis of epithelium from surgical specimens from IBD and control patients (not shown). These data are consistent with findings from Gamo et al demonstrating elevated Sprouty2 expression in adult IBD patients 39 .…”
Section: Sprouty2 Levels Are Increased In Human Ibd and Negatively Csupporting
confidence: 93%
“…Likewise, the Monoamine oxidase inhibitor Procarbazine may have the potential to modulate neurotransmitters and immune responses and BCR-ABL kinase inhibitors such as Dasatinib and RAF inhibitors like Vemurafenib, AZ-628, and PLX-4720 might indirectly impact immune pathways, offering insights into IBD modulation ( 80 , 81 ). Additionally, mTOR inhibitors, represented by WYE-354, and SYK inhibitors like Fostamatinib are under investigation for their anti-inflammatory effects ( 82 , 83 ) and MEK inhibitors, including PD-0325901 and MEK1-2-inhibitor, target pathways associated with inflammation and immune responses ( 84 ). It’s worth acknowledging the dichotomous findings regarding the impact on IBD as certain reports suggested RAF/MEK inhibitors to potentially promote IBD in humans and mice ( 85 , 86 ), while others have indicated that MEK inhibitors hold promise in improving diarrhea and histological scores in a murine colitis model ( 84 ), and RAF inhibition has induced clinical remission in CD patients ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mTOR inhibitors, represented by WYE-354, and SYK inhibitors like Fostamatinib are under investigation for their anti-inflammatory effects ( 82 , 83 ) and MEK inhibitors, including PD-0325901 and MEK1-2-inhibitor, target pathways associated with inflammation and immune responses ( 84 ). It’s worth acknowledging the dichotomous findings regarding the impact on IBD as certain reports suggested RAF/MEK inhibitors to potentially promote IBD in humans and mice ( 85 , 86 ), while others have indicated that MEK inhibitors hold promise in improving diarrhea and histological scores in a murine colitis model ( 84 ), and RAF inhibition has induced clinical remission in CD patients ( 87 ). Lastly, compounds such as the Cannabinoid receptor antagonist O-1918, cyclooxygenase inhibitor Valdecoxib, and Histamine receptor antagonist Loratadine are all associated with anti-inflammatory pathways ( 88 90 ).…”
Section: Discussionmentioning
confidence: 99%